Optimalisasi Pemberdayaan Masyarakat RT 4 dan RT 5A RW 5 di Kelurahan Langensari Kabupaten Semarang - Tya Lestari; Ida Sofiyanti; Ratih Kumalasari; Irma Suryani (Universitas Ngudi Waluyo, 2022)
Community empowerment is an activity to increase community participation in meeting the needs of life and solving problems experienced by the community, especially in the health problems of mothers and children. The activity is carried out through the Community Midwifery Care practice program which is a community service-based activity to increase students' empathy for the condition of the community and its environment. The Practice of Community Midwifery Care for Midwife Professional Education Study Program is carried out in Langensari Village RT.4 and RT.5A RW.05 with service methods such as counseling, training, demonstrations and simulations. The results of the activity showed a positive response from Langensari Village and high active community participation, including participating in work programs carried out by female students. Problems that arise in the field of health, especially in mothers and children, adolescents, and the elderly. Management has been carried out optimally with the results of: (1) Increasing the knowledge of pregnant women about the importance of the Childbirth Planning and Prevention of Complications (P4K) Program and sticking P4K stickers at home; (2) Increasing the knowledge of breastfeeding mothers about the importance of Exclusive Breast Milk (ASI) in infants aged 1-6 months; (3) Increased knowledge in adolescents by conducting counseling on adolescent reproductive health and about Sexually Transmitted Diseases (STDs); (4) There is an increase in the knowledge of Couples of Childbearing Age (PUS) about the importance of using contraceptives after childbirth; (5) There is an increase in the elderly's knowledge about health in the elderly, the lifestyle of the elderly and balanced nutritional food for the elderly. The community in Langensari Village plays an active role and participates in activities or work programs carried out by students. AbstrakPemberdayaan masyarakat merupakan kegiatan peningkatan partisipasi masyarakat dalam pemenuhan kebutuhan hidup dan menyelesaikan permasalahan yang dialami masyarakat terutama pada maslah kesehatan pada ibu dan anak. Kegiatan dilaksanakan melalui program praktek Asuhan Kebidanan Komunitas yang merupakan aktivitas berbasis pengabdian masyarakat untuk meningkatkan empati mahasiswa terhadap kondisi masyarakat dan lingkungannya. Praktek Asuhan Kebidanan Komunitas Prodi Pendidikan Profesi Bidan dilaksanakan di Kelurahan Langensari RT.4 dan RT.5A RW.05 dengan metode pengabdian seperti penyuluhan, pelatihan, demonstrasi dan simulasi. Hasil kegiatan menunjukkan adanya respon positif dari Kelurahan Langensari serta partisipasi aktif masyarakat yang tinggi, diantaranya mengikuti program kerja yang dilakukan oleh mahasiswi. Masalah yang muncul dalam bidang kesehatan khususnya pada ibu dan anak, remaja, serta lansia. Penatalaksanaan telah dilakukan secara optimal dengan hasil: (1) Peningkatan pengetahuan ibu hamil tentang pentingnya Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) dan penempelan stiker P4K di rumah; (2) Peningkatan pengetahuan ibu menyusui tentang pentingnya Air Susu Ibu (ASI) Ekslusif pada bayi umur 1-6 bulan; (3) Terjadinya peningkatan pengetahuan pada remaja dengan dilakukannya penyuluhan kesehatan reproduksi remaja dan tentang Penyakit Menular Seksual (PMS); (4) Terjadinya peningkatan pengetahuan Pasangan Usia Subur (PUS) tentang pentingnya penggunaan alat kontrasepsi setelah melahirkan; (5) Terjadinya peningkatan pengetahuan lansia tentang kesehatan pada lansia, pola hidup lansia dan makanan gizi seimbang untuk lansia. Masyarakat di Kelurahan Langensari ikut berperan aktif dan berpartisipasi dalam kegiatan atau program kerja yang dilakukan oleh mahasiswa.